John Law and the Mississippi scheme an anthology - Defoe, Daniel 1660-1731 (Newton Page, 2014)
This collection includes: 'The Chimera', a prophetic critique and damnation of John Law's Mississippi Scheme, 'The Case of Mr. Law Truly Stated', a propagandist attack upon Law's return to Britain after the collapse of the Mississippi Scheme and his expulsion from France, and, selected journalism spanning 1719-1722 cataloging Defoe's contemporaneous coverage of the rise and fall of John Law
Keywords: Law, John / 1671-1729; South Sea Company; Financial crises / History / 18th century / Sources; Financial crises; 1700-1799; History; Sources